2019
DOI: 10.1016/j.hrthm.2019.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit juice prolongs the QT interval of healthy volunteers and patients with long QT syndrome

Abstract: BACKGROUND The list of medications linked to drug-induced long QT syndrome (LQTS) is diverse. It is possible that food products too have QT-prolonging potential.OBJECTIVE We tested the effects of grapefruit juice on the QT interval with the methodology used by the pharmaceutical industry to test new drugs. METHODSThis was an open-label, randomized, crossover study with blinded outcome evaluation, a thorough QT study of grapefruit juice performed according to the Guidelines for the Clinical Evaluation of QT/QTc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…These include avoidance of QT‐prolonging drugs (see below) and identification and correction of electrolyte abnormalities caused by diarrhea, vomiting, metabolic conditions or imbalanced diets for weight loss . The evidence that grapefruit juice prolongs the QT interval in healthy volunteers and patients with LQTS also suggests a role of “proarrhythmic food” …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include avoidance of QT‐prolonging drugs (see below) and identification and correction of electrolyte abnormalities caused by diarrhea, vomiting, metabolic conditions or imbalanced diets for weight loss . The evidence that grapefruit juice prolongs the QT interval in healthy volunteers and patients with LQTS also suggests a role of “proarrhythmic food” …”
Section: Resultsmentioning
confidence: 99%
“…63 The evidence that grapefruit juice prolongs the QT interval in healthy volunteers and patients with LQTS also suggests a role of "proarrhythmic food". 64 Regarding sports participation, previous guidelines by the 36th In asymptomatic patients, the protective benefit of an ICD should be balanced against the risk of device-related complications and the influence of age and gender should be considered. For example, for a male with LQTS who has remained asymptomatic by the age of 25 years, the risk of ever developing an arrhythmia is very small even in the absence of therapy.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…Maximum QTc prolongation occurs at 4-5 h after the ingestion of grapefruit juice by normal individuals, being the mean QTc of 12.5 ms [6] to 14.0 ms [7]. In patients with cLQTS, mean QTc prolongation was 21.8 ms and a maximum of 48.5 ms was registered [7].…”
Section: Discussionmentioning
confidence: 97%
“…Different trials have confirmed that grapefruit juice prolongs the QTc in healthy individuals [6,7] and in patients with cLQTS [7]. The molecular basis of this QTc prolongation is due to the inhibition of HERG (also known as KCNH2, which is a potassium channel responsible for the rapid delayed rectifier current I Kr [2] of the phase 3 of the cardiac cells action potential) by flavonoids present on grapefruit, being the naringenin, morin, and hesperetin the three most potent inhibitors [6].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding grapefruit juice speci cally, Chorin et al (Chorin et al, 2019) recently established in a well powered randomized TQT study in healthy volunteers, that the length of the QT segment on the ECG corrected for heart rate (i.e. QTc) increased signi cantly as soon as three hours after drinking 1 liter of grapefruit juice.…”
Section: Introductionmentioning
confidence: 99%